2016
DOI: 10.1021/acs.jproteome.6b00429
|View full text |Cite
|
Sign up to set email alerts
|

HILIC and ERLIC Enrichment of Glycopeptides Derived from Breast and Brain Cancer Cells

Abstract: Aberrant glycosylation has been linked to many different cancer types. In breast cancer metastasis to the brain the blood brain barrier, a region of the brain that regulates the entrance of ions, diseases, toxins, etc., fails to block breast cancer cells from crossing. Here we present a study of identifying and quantifying the glycosylation of six breast and brain cancer cell lines using hydrophilic interaction liquid chromatography (HILIC) and electrostatic repulsion liquid chromatography (ERLIC) enrichments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 36 publications
0
79
0
Order By: Relevance
“…Several methods and bioinformatics approaches based on additional qualitative information have been developed to improve the identification of glycopeptides . The most common is the use of parallel analysis of glycopeptides trimmed or deglycosylated by enzymatic treatment such as PNGase F . Chen et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods and bioinformatics approaches based on additional qualitative information have been developed to improve the identification of glycopeptides . The most common is the use of parallel analysis of glycopeptides trimmed or deglycosylated by enzymatic treatment such as PNGase F . Chen et al.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods and bioinformatics approaches based on additional qualitative information have been developed to improve the identification of glycopeptides [26]. The most common is the use of parallel analysis of glycopeptides trimmed or deglycosylated by enzymatic treatment such as PNGase F [27][28][29]. Chen et al reported an approach based on the reduction of the glycan structures to a mannose core that resulted in an increased confidence of the glycopeptide assignments [27].…”
Section: Prediction Of the Retention Time Windowsmentioning
confidence: 99%
“…Dynamic exclusion was enabled to exclude ions repeated within 20 seconds. The energy used for HCD was 45% normalized collision energy optimized in previous studies (7577) while 30% normalized collision energy was used for CID which was also previously optimized (78). A mass tolerance of 10 ppm was used for extracted ion chromatograms (EICs) of full MS data.…”
Section: Methodsmentioning
confidence: 99%
“…HILIC is suitable for the analysis of polar analytes which are inadequately retained in RP-LC [1]. HILIC was successfully applied to glycopeptide enrichment [7,8], released glycan analysis [9,10], and separation of different glycoforms of peptides [11]. Although the directed analysis of glycoproteins provides site-specific information on glycans, the common approach to characterize glycans in HILIC is their enzymatic or chemical releas LC/MS analysis [12].…”
Section: Introductionmentioning
confidence: 99%